OCCUPATIONAL EXPOSURE TO LOCALIZED VIBRATIONS USING PORTABLE MECHANICAL BRUSH CUTTER IN COFFEE CROP - Oliveira Junior, Geraldo Gomes de; Silva, Adriano Bortolotti da; Cunha, Irlon de Ângelo; Aparecido, Lucas Eduardo de Oliveira; Sabino, Paulo Henrique de Siqueira (Coffee Science - ISSN 1984-3909, 2019)
The use of portable brush cutter may expose workers to localized vibrations, from the transfer of mechanical vibration of the tool to the operator’s hands and arms. With this in mind, the objective in this study was to quantify the levels of occupational vibration transmitted to the hands and arms of the portable brush cutter operators under routine working conditions in the coffee crop. The vibration levels transmitted to the operator’s hands were measured during activity with portable brush cutters. The experimental design was completely randomized (CRD) in a factorial scheme (2 x 2) combined with two types of grip (Circular cable (CC) and double grip handle (DGH) with two types of tip cutting blades (2TB and 3TB). The data acquisition occurred from the use of the vibration meter SV 103, SVANTEK with triaxial accelerometer, installed on each of the worker’s hand at the contact point with the tool. The results demonstrated that the 2.5 ms-2 action level determined by NR 09 and NHO 10 was exceeded under all conditions of the present study. The highest accelerations were quantified in the operation of the brush cutter equipment with CC, reaching the daily exposure limit of 5 ms-2 allowed for an 8-hour of working day. The resulting acceleration of the DGH equipment was on average 37.45% lower than the operation with the CC equipment. The results bring indicatives of occupational advantages in the selection of these types of accessories for brush cutters, in order to mitigate the effects of exposure to HAV in extended use situations